2002
DOI: 10.1249/00149619-200212000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Managing Blisters in Competitive Athletes

Abstract: Friction blisters can have a negative effect on an individual's ability to perform his or her sport or duties. In a recent study, 69% of soldiers participating in a 20-km road march were found to have blisters, 10% of whom required medical intervention. Blistering of the feet is one of the most common injuries sustained by runners while training and racing. Although most blisters are minor and can be treated conservatively, others can lead to intense pain, cellulitis, and even sepsis. The best way to treat fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 8 publications
0
22
0
2
Order By: Relevance
“…Aluminium-based antiperspirants, which aim to block the sweat glands, have been used to prevent excessive perspiration of foot skin [21,32]. Knapik et al (1998) found that the risk of blister formation was reduced by 12% with the use of an antiperspirant and the lowest incidence of blisters was seen after 3 days of antiperspirant use [26].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminium-based antiperspirants, which aim to block the sweat glands, have been used to prevent excessive perspiration of foot skin [21,32]. Knapik et al (1998) found that the risk of blister formation was reduced by 12% with the use of an antiperspirant and the lowest incidence of blisters was seen after 3 days of antiperspirant use [26].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Therefore the antiperspirant effect observed in this study is not representative of regular use. Antiperspirants prevent excessive sweating by plugging sweat glands [32] and when applied in successive days the action of the antiperspirant accumulated for greater efficacy. However, we would argue that for foot blisters, use of an antiperspirant is probably limited to specific events where a risk of blister is expected, such as a running event or use of new footwear.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Friction blisters as a result of prolonged bouts of exercise frequently lead to cellulitis in soldiers 20. The infection is more common in the legs, but facial and orbital cellulitis can occur 21.…”
Section: Superficial and Uncomplicated Infectionmentioning
confidence: 99%
“…Shearing forces in these areas cause relative movement of the upper and lower layers of the epidermis, leading to mechanical fatigue and reduced intercellular adhesion [95]. Primary risk factors include ill-fitting equipment (clothing, baseball mitt, shoes), sweat, heat, and prolonged activity [94,96,97].…”
Section: Friction Bullaementioning
confidence: 99%